2018
DOI: 10.1002/mats.201700070
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of DNA Condensation by PAMAM Dendrimer

Abstract: In this study, dissipative particle dynamics is employed to investigate the complexation of poly(amido amine) dendrimer and single‐stranded DNA (ssDNA). A coarse‐grained model for ssDNA is constructed, which reproduces correctly the conformational behavior of the ssDNA molecules. The effects of pH, dendrimer generation, ionic strength, and dendrimer/ssDNA charge ratio on DNA–dendrimer complexes are explored. Simulation results show that ssDNA molecules can be significantly condensed by dendrimers and stable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…One well-known example is the Arg-Gly-Asp (RGD) peptide, which has a strong affinity to αvβ3 integrin, which is expressed at high levels on the surface of tumor microvasculature as well as some cancer cells [85]. In 2016 [86], Ma and co-workers investigated a peptide called RGD-TAT (RGD attached to amino acids 49–57 of the HIV TAT protein that functions as a “cell penetrating peptide”) and attached it to G4 PAMAM to produce a new RGD-TAT-PEG-PAMAM (RTPP) nanocarrier that could encapsulate methotrexate (MTX) as a model drug. In vitro targeting ability of the complexes was studied in HepG2 and MCF7 cells (expressing αvβ3 integrin at high and low levels respectively) was studied using a fluorescent indicator.…”
Section: Pamam Dendrimersmentioning
confidence: 99%
See 2 more Smart Citations
“…One well-known example is the Arg-Gly-Asp (RGD) peptide, which has a strong affinity to αvβ3 integrin, which is expressed at high levels on the surface of tumor microvasculature as well as some cancer cells [85]. In 2016 [86], Ma and co-workers investigated a peptide called RGD-TAT (RGD attached to amino acids 49–57 of the HIV TAT protein that functions as a “cell penetrating peptide”) and attached it to G4 PAMAM to produce a new RGD-TAT-PEG-PAMAM (RTPP) nanocarrier that could encapsulate methotrexate (MTX) as a model drug. In vitro targeting ability of the complexes was studied in HepG2 and MCF7 cells (expressing αvβ3 integrin at high and low levels respectively) was studied using a fluorescent indicator.…”
Section: Pamam Dendrimersmentioning
confidence: 99%
“…In vitro targeting ability of the complexes was studied in HepG2 and MCF7 cells (expressing αvβ3 integrin at high and low levels respectively) was studied using a fluorescent indicator. Their results showed that HepG2 cells (over-expressing αvβ3 compared to MCF7cells) showed higher cytotoxicity due to a combination of RGD recognition and the TAT cell-penetrating ability [86]. Effective delivery of anticancer drugs to brain tumors is difficult because of limited penetration through the “blood-brain-barrier” (BBB).…”
Section: Pamam Dendrimersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to biopolymers, some other nanomaterials have been proposed as the drug carriers with controllable release efficiency and high loading capability. For example, Su et al . pointed that as gene delivery carriers, PAMAM dendrimers can compact the single‐stranded DNA (ssDNA) significantly at neutral or low pH value.…”
Section: Modeling and Simulation Of Ncs Delivery Through Biological Bmentioning
confidence: 99%
“…The interaction between NCs and drug molecules, which determines the containment and release of drugs, becomes a key in drug delivery technique. Generally, in order to enhance the loading content and release efficiency, the drug molecules are loaded into carriers via hydrophobic interactions, electrostatic interactions, hydrogen bonding, π–π stacking, and covalent interactions . By engineering hydrophobic interaction between protein‐based NCs and small guest molecules, Ren et al .…”
Section: Modeling and Simulation Of Ncs Delivery Through Biological Bmentioning
confidence: 99%